(untitled) (Global Journal of Management and Business Research, 2020)
Introduction to the Idea of the Paper he idea of nations has been born from the concept of the Westphalia treaty that was incorporated in Europe However that treaty itself is a problem in terms of understanding the concept of nation in the world of today the notion of Eurocentric world has moved a long time past and the emergence of the postcolonial countries albeit some of them least moderate or very successful respectively Daniel 2005 The word nation and sovereignty which are mentioned together in the title generally represent the biggest common place meaning which is determined through Freedom of choice